Determinants of stunting in babies under five years - Harahap, Dewi Syahriani; Nababan, Donal; Silitonga, Evawani Martalena (Science Midwifery, 2024)
The aim of this research is to analyze the determinants of stunting in toddlers. This research is an analytical survey research with a cross-sectional design explaining the relationship between knowledge, parenting patterns, socio-economic and access to sanitation, exclusive breastfeeding and the incidence of stunting in toddlers. This research was conducted in the Hutagodang health center working area, South Labuhan Batu Regency from January to August 2023. The population was mothers who had toddlers and the entire population was sampled. The research results show that there is a significant relationship between knowledge, parenting patterns, socio-economic factors, exclusive breastfeeding and the incidence of stunting in toddlers. There is no relationship between access to sanitation and the incidence of stunting in toddlers. The most dominant factor in the incidence of stunting in toddlers is knowledge with an exposure (β) of 4,558 greater than the exposure (β) of other variables. Parents of toddlers are expected to increase their knowledge about stunting, its impacts and how to prevent it. This can be done through printed media such as leaflets, brochures, magazines which have been provided by the community health center at the village hall, village office, posyandu and village health post, electronic media or outreach carried out by village midwives, community health center officers and village officials.